The Archaeology Of Gua Tupak From 1,190 B.P. To 170 B.P. In Bau, Sarawak - Gani, Nicholas (2010)

(untitled)
In November and December 2007, an archaeological survey was conducted by the author and a research team from the Centre for Global Archaeological Research, Universiti Sains Malaysia, Penang with the cooperation of the Sarawak Museum Department, Kuching in the limestone caves of the Bau area, southwest Sarawak in order to search for a site for the author’s Master of Arts (MA) study. The result of the survey determined Gua Tupak to be a highly potential site and consequently, excavations were carried out at the site in February and March 2008. The excavations at Gua Tupak yielded valuable archaeological data that could aid in providing information on the prehistory of the site and the Bau area. The archaeological data include various types of artefacts such as shell remains, animal bones, ceramic sherds and stone artefacts. In addition, charcoal and shell samples were collected for radiocarbon dating, soil samples were collected for palynological analysis and soil profiles of the excavated trenches were recorded. Results of the analyses of artefacts and interpretations of the archaeological data recovered from Gua Tupak suggest that the site was used as a temporary habitation site or shelter with two main phases of occupation; the Early Phase with a radiocarbon date of around 1,190 ± 40 B.P., and the Late Phase with radiocarbon dates ranging from 270 ± 50 B.P. to 170 ± 40 B.P.